2021
DOI: 10.3389/fmars.2021.766903
|View full text |Cite
|
Sign up to set email alerts
|

How and to What Degree Does Physical Structure Differ Between Natural and Artificial Habitats? A Multi-Scale Assessment in Marine Intertidal Systems

Abstract: Marine infrastructures are increasing, generating a variety of impacts and introducing artificial habitats which have low ecological value and support assemblages that differ significantly from those on natural rocky coasts. While in the past there was little ecological consideration as to how artificial structures were built, now the trend is to look for “greener” designs inspired by or mimicking nature. These greening efforts have had a strong focus on enhancing physical habitat structure to support more div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…As degraded habitats and artificial coastal defences typically lack the quantity and range of habitat features normally found in natural shores (Lawrence et al., 2021; Nash et al., 2013, but also see Grasselli & Airoldi, 2021), the creation of microhabitats is an important form of active interventions for biodiversity enhancement (Loke et al., 2015). The various sizes of microhabitats in the Complex fish house were designed to provide more unique niche spaces for fishes compared to the Simple fish house.…”
Section: Discussionmentioning
confidence: 99%
“…As degraded habitats and artificial coastal defences typically lack the quantity and range of habitat features normally found in natural shores (Lawrence et al., 2021; Nash et al., 2013, but also see Grasselli & Airoldi, 2021), the creation of microhabitats is an important form of active interventions for biodiversity enhancement (Loke et al., 2015). The various sizes of microhabitats in the Complex fish house were designed to provide more unique niche spaces for fishes compared to the Simple fish house.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies have pointed out that artificial substrates do not act as natural surrogates (Bulleri & Chapman, 2004;Burt et al, 2009) due to differences in material type, substrate complexity, inclination, orientation and wave exposure among others (Hanlon et al, 2018;Evans et al, 2021;Grasselli & Airoldi, 2021;Hartanto et al, 2022). However, few exceptions have evidenced that artificial substrates are not generally ecologically poor (Gacia et al, 2007;López, 2022;Baxter et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These new artificial rocky substrates support distinct assemblages, which are generally considered less biodiverse with low ecological value compared to natural rocky marine habitats (Grasselli & Airoldi, 2021;Sedano et al, 2021;Doods et al, 2022). Most studies have focused on comparing community structures between natural and artificial habitats based on differences in material type (Hartanto et al, 2022), substrate complexity (Evans et al, 2021), substrate inclination (Grasselli & Airoldi, 2021) and orientation among others (Hanlon et al, 2018). Generally, these studies have concluded that artificial structures do not function as real surrogates of natural rocky habitats (Bulleri & Chapman, 2004Burt et al, 2009;Sedano et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst it appears that surface properties may influence microbial communities early on, it appears that communities converge later in the ecological succession process. Other factors, such as site or surface aspect (north-south directionality) and orientation of material (e.g., horizontal/vertical), may have greater influence on community composition (Firth et al 2015;Amstutz et al, 2021Amstutz et al, , 2023, with effects potentially even larger than those from surface complexity (Grasselli and Airoldi, 2021). This evolving picture can help industry focus resources on other aspects of material choice, including carbon footprint (Dennis et al 2018;Dauvin et al 2022) and chemical pollution of concrete (Kress et al, 2002;McManus et al, 2018).…”
Section: Wider Consideration Of Materials and Substrate Typesmentioning
confidence: 99%
“…-Consideration of variability with orientation differences (Grasselli and Airoldi, 2021). Limited metrics measured.…”
Section: Greening Of Grey Infrastructure (Ggi) On Marine Artificial S...mentioning
confidence: 99%